Lost in Amazon: Evidencing the southern extension of the geographic distribution of Linné's two-toed sloth (Choloepus didactylus) - Castro, Arlison Bezerra; Melo-Dias, Mateus [UNESP]; Santos, Tatiane Pires; Custódio, Rogério José; de Jesus Rodrigues, Domingos; Rosa, Clarissa Alves (Wiley, 2024)
We documented new records of Choloepus didactylus extending up to 820 km south of its current geographic distribution. These records, and others found in literature for the central-southern Amazon, evidence a southern expansion of about 30% of the known species' area of occurrence and help shedding light on decades of uncertainties about its real distribution. Abstract in Portuguese is available with online material.
Keywords: arboreal mammal; arc of deforestation; area of occurrence; Brazil; central-southern Amazon; Mato Grosso; neotropical rainforest; xenarthra